1985
DOI: 10.1063/1.526675
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of lattice sums and Madelung’s constant

Abstract: The lattice sums involved in the definition of Madelung's constant of an NaCI-type crystal lattice in two or three dimensions are investigated. The fundamental mathematical questions of convergence and uniqueness of the sum of these, not absolutely convergent, series are considered. It is shown that some of the simplest direct sum methods converge and some do not converge. In particular, the very common method of expressing Madelung's constant by a series obtained from expanding spheres does not converge. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
2

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 5 publications
4
73
0
2
Order By: Relevance
“…is divergent which is physically unsatisfactory. The convergence properties of such sums have been extensively investigated (Borwein et al, 1985;Chaba and Pathria, 1975, 1976a,b, 1977. The sum (44) is an alternating and conditionally convergent sum.…”
Section: Condensed Matter Physicsmentioning
confidence: 99%
“…is divergent which is physically unsatisfactory. The convergence properties of such sums have been extensively investigated (Borwein et al, 1985;Chaba and Pathria, 1975, 1976a,b, 1977. The sum (44) is an alternating and conditionally convergent sum.…”
Section: Condensed Matter Physicsmentioning
confidence: 99%
“…It is interesting to note that summation over regions that may seem to be natural can diverge. As an example, for a 3-dimensional NaCl-type ionic crystal, it was shown that this lattice sum does not converge over expanding spheres [3], expanding ellipsoids, and some specific expanding polygons [4], but it would converge for expanding cubes [3]. The direct summation method is not practical due to the slow rate of convergence.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in what order one should sum the terms of the series (2) to obtain the Ewald's result? Borwein, et al [3] showed that for NaCl-type crystals, summing over cubes would yield the Ewald result. It is interesting to note that ′ n∈Z 3 |n + r| −1 is not a convergent series and since all of the summands are positive, partial sums of this series would be unbounded.…”
Section: Introductionmentioning
confidence: 99%
“…For the simple cubic NaCl structure one can find a much faster and more accurate path to the Madelung constant based on analytical formulae of Borwein et al (7). This is discussed in Sect.…”
Section: Numerical Considerationsmentioning
confidence: 99%
“…In the macroscopic limit when N becomes large this quantity will go to minus infinity. If we divide it by the number of (neutral) molecules, N3/2, we get the electrostatic energy per molecule in the form [7] @ = lim qN N-co Note that N should be even if the macroscopic piece is to be neutral; otherwise it has charge minus one, but this does not affect convergence.…”
Section: Electrostatic Energymentioning
confidence: 99%